Evaluación de hongos antagonistas de botrytis cinerea pers., en plantaciones de mora, Costa Rica - Marín-Chacón, María Angélica (2017)
Evaluation of Botrytis cinerea Pers., antagonist fungi in blackberry plantations of Costa Rica. Isolation, identification, in vitro and field evaluation of antagonistic fungi of Botrytis cinerea was conducted on blackberry plantations. Collection of antagonistic organisms was carried out in Cartago in the towns of La Luchita, Bajo Canet, Garden and Division during 2012. From the fruits, a group of 43 isolates belonging to 10 different fungi genera were obtained: Aspergillus sp., Bispora sp., Cladosporium spp., Colletotrichum sp., Curvularia sp., Macrophoma sp., Paecilomyces spp., Pestalotia spp., Rhizoctonia sp., and Trichoderma spp. All isolates were tested for antagonistic capacity by dual culture technique, substrate competition and antibiosis. Only isolates that exceeded 70% of the PGI were selected, and these were 4 isolates (BC1, J14, J2.2 and J2.1) of the genus Trichoderma spp. Field tests were done by using 3 isolates (BC1, J2.2 and J2.1) from the present work and 3 (BV1, SM13B and SM18) of the same genus from a previous work. Field trials were carried out in 2013. Trichoderma spp. isolates which had statistically (p≤0.0001) greater effect on Botrytis cinerea were BV1 and BC1, showing less affected fruits.